Health in overweight children: 2-year follow-up of Finnmark Activity School-a randomised trial - Kokkvoll, Ane Sofie; Grimsgaard, Sameline; Steinsbekk, Silje; Flægstad, Trond; Njølstad, Inger (Archives of Disease in Childhood, 2014)
This article is part of Ane Kokkvoll's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/6964